Dysfunctions of Time Management in the Working Process of Managers - Ulrych, Wojciech (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The paper presents the essence of time management in a managerial work taking into account both the unresolved issues for decades in this area, as well as new issues arising from the process of globalization. The previous problems concern too long working hours for managers and fragmented structure of operations while the short time spent for each of them. These problems have been still actual but the new ones have appeared. They are associated with the ability to delegate tasks, manage business processes in the light of the criterion of time, the requirements of different generations as to work - life balance issue, and in the case of multinational companies refers to CEOs time management on business trips. The potential dysfunctions of HRM function in manager work being under time pressure were also highlighted.